Optimisation of a Lithium Bromide (LiBr) Absorption Solar Cooling System - Kalogirou, Soteris A.; Florides, Georgios A. (My University, 2002)
The objective of this paper is to present the optimisation of the various components of a lithium bromide (LiBr) absorption solar cooling system such as the type, slope and area of solar collector and storage tank size. The collector types considered are the flat plate, compound parabolic and evacuated tube collectors. The optimisation is based on an energy benefit analysis, i.e., the amount of useful energy collected against the life cycle cost of the solar system. The system is modelled with the TRNSYS computer program using data for a typical meteorological year (TMY) for a hot climate (Nicosia, Cyprus) and a typical house with a total floor area of 196 m2. The results indicate that for the present application the compound parabolic collector is the most cost effective whereas the optimum collector area is 15 m2, the optimum slope of the collector is 30° and the storage tank size is 600 lt.
Keywords: Lithium bromide absorption; Parabolic collector